2008
DOI: 10.1182/blood-2008-03-147645
|View full text |Cite
|
Sign up to set email alerts
|

MYC stimulates EZH2 expression by repression of its negative regulator miR-26a

Abstract: The MYC oncogene, which is commonly mutated/amplified in tumors, represents an important regulator of cell growth because of its ability to induce both proliferation and apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
304
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(332 citation statements)
references
References 45 publications
24
304
0
4
Order By: Relevance
“…The functional overlap between MYCN and c-MYC is further substantiated by the identification of a c-MYC-translocated neuroblastoma tumor with a mRNA, miRNA and genomic profile that is typical for a MYCN-amplified tumor. It is also perfectly in line with previous reports on miRNAs commonly regulated by c-MYC and MYCN (Chen and Stallings, 2007;Chang et al, 2008;Sander et al, 2008;Schulte et and with the observation that MYCN can functionally replace c-MYC in murine development (Malynn et al, 2000). Whether c-MYC is capable of replacing MYCN remains to be determined but could further corroborate these findings.…”
Section: Discussionsupporting
confidence: 91%
“…The functional overlap between MYCN and c-MYC is further substantiated by the identification of a c-MYC-translocated neuroblastoma tumor with a mRNA, miRNA and genomic profile that is typical for a MYCN-amplified tumor. It is also perfectly in line with previous reports on miRNAs commonly regulated by c-MYC and MYCN (Chen and Stallings, 2007;Chang et al, 2008;Sander et al, 2008;Schulte et and with the observation that MYCN can functionally replace c-MYC in murine development (Malynn et al, 2000). Whether c-MYC is capable of replacing MYCN remains to be determined but could further corroborate these findings.…”
Section: Discussionsupporting
confidence: 91%
“…It is not fully established how MYCBP regulates these E-box-containing genes because of growing evidence about the function of MYCBP (Furusawa et al, 2001Yukitake et al, 2002;Ishizaki et al, 2006), but there is evidence suggesting that MYCBP acts, at least in part, through modulating the transactivation activity of c-Myc to enhance the transcription of these genes (Taira et al, 1998;Sakamuro and Prendergast, 1999). Recent studies showed that some c-Myc-mediated miRNAs were implicated in tumorigenesis, embryonic stem cell differentiation and glutamine metabolism (He et al, 2005;O'Donnell et al, 2005;Dews et al, 2006;Chang et al, 2008;Sander et al, 2008;Gao et al, 2009;Lin et al, 2009;Mestdagh et al, 2009). However, only two miRNAs were found to modulate c-Myc, whereas c-Myc is not their significant targets (Sampson et al, 2007;Lal et al, 2009).…”
Section: Mir-22 Might Constitute a Feedback Loop With C-myc And Mycbpmentioning
confidence: 99%
“…In humans, the LET-7 has been shown to act as a tumour suppressor, via targeting the human RAS oncogene (40)(41)(42)(43). Similarly, as explained previously, miR-26A also acts in a tumour suppressor capacity (18,38,39,47). Evaluation of the role of these miRs in B-cell lymphoma pathogenesis merits further investigation.…”
Section: Discussionmentioning
confidence: 58%
“…tures of both entities included up-regulated microRNAs of the known oncomiR miR-17-92 (27) as well as downregulated microRNAs recognised as tumour suppressors, including miR-26A (38,39) and members of the the LET-7 family (40)(41)(42)(43). Thus, these signatures correctly predicted the prognostic significance assigned to the immunophenotype, especially that of the ABC-type.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation